2021
DOI: 10.1186/s40663-021-00320-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plant debris and carbon stocks across a subalpine forest successional series

Abstract: Background As a structurally and functionally important component in forest ecosystems, plant debris plays a crucial role in the global carbon cycle. Although it is well known that plant debris stocks vary greatly with tree species composition, forest type, forest origin, and stand age, simultaneous investigation on the changes in woody and non-woody debris biomass and their carbon stock with forest succession has not been reported. Therefore, woody and non-woody debris and carbon stocks were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…In theory, forest succession could influence the shifts in soil microbial communities in at least the following ways. First, the quality and quantity of woody and non-woody debris on the forest floor vary greatly with forest succession [22], and the related changes in substrate quality and quantity alter the composition and diversity of soil microbial communities [23]. Second, soil temperature and moisture can vary greatly with forest succession owing to the changes in canopy structure and understory cover [24,25]; both soil temperature and moisture are key factors in determining the composition and structure of soil microbial communities [15,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, forest succession could influence the shifts in soil microbial communities in at least the following ways. First, the quality and quantity of woody and non-woody debris on the forest floor vary greatly with forest succession [22], and the related changes in substrate quality and quantity alter the composition and diversity of soil microbial communities [23]. Second, soil temperature and moisture can vary greatly with forest succession owing to the changes in canopy structure and understory cover [24,25]; both soil temperature and moisture are key factors in determining the composition and structure of soil microbial communities [15,26].…”
Section: Introductionmentioning
confidence: 99%
“…As affected by long-term natural disturbances such as earthquakes, debris flows and snowslides, and commercial logging of natural forests, subalpine forest communities of different successional stages have been widely observed in the subalpine forest region [34,35]. To date, changes in woody and non-woody debris stocks across a subalpine forest successional series [22] and changes in soil microbial diversity with gap size [36] and along environmental gradients [37] in the subalpine forest region have been documented. Nevertheless, little information is available on soil microbial community shifts across the subalpine forest successional series.…”
Section: Introductionmentioning
confidence: 99%
“…Forest type affects the species composition and productivity of the ecosystem, with a significant effect on the forest ecosystem C and N stocks (Liu et al 2018;Wang et al 2021). Previous studies have documented that C and N concentration vary significantly among tree species and plant organs (Yerena Yamallel et al 2012;Yao et al 2015;Liang et al 2018;Ma et al 2018;Jing et al 2020;Zhang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…N-fixers, as some Fabaceae tree species, exhibit higher leaf N concentration than non-fixer species (Taylor and Ostrowsky 2019). Also, many studies reported that the amount and quality of plant woody debris, and non-woody debris, change with forest type and structure, and may affect the biodegradability of soil organic matter (Cools et al 2014;Mendoza et al 2014b;Moreira et al 2019;Wang et al 2021). This is also strongly affected by species composition (Wang et al 2019) and stand age (Schilling et al 2016;Lachowicz et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation